Estate & Urban Sectors in Sri Lanka: Vulnerabilities Requiring Focused Attention - Enoka Wickramasinghe (College of Community Physicians of Sri Lanka, 2021)
Professor Dulitha Nandanie Fernando (1944-2021) was an exemplary leader exhibiting the art of true collaboration and integration through the projects she was involved in. She was a pioneering researcher in nutrition surveys conducted among vulnerable populations in Sri Lanka, which had assisted in quantifying the magnitude of the issue to take necessary policy decisions and targeted interventions (1-2). She has provided sound evidence for necessary action to prevent the wide spectrum of malnutrition and low birth weight in estate populations and overweight/obesity and determinants among urban people. She has trained and mentored the second and third generations of consultant community physicians and researchers in the field of nutrition who would continue to cascade the changes she desired to see among vulnerable populations in Sri Lanka.   In acknowledgement of Professor Dulitha Fernando's work among vulnerable populations, cover story of this issue is dedicated to under-privileged persons in the estate and urban sectors in Sri Lanka.